Revisiting the Relationship Between Internal Focus and Balance Control in Young and Older Adults - Chow, Victoria W. K.; Ellmers, Toby J.; Young, William R.; Mak, Toby C. T.; Wong, Thomson W. L. (Frontiers in Neurology, 2019)
Research highlights the detrimental effect that directing too much conscious attention towards movement can have on postural control. While this concept has received support from many studies, recent evidence demonstrates that this principle does not always translate to aging clinical populations. Given the increasing clinical interest in this topic, the current study evaluated if the original notion (that an internal focus results in compromised balance performance) is upheld in young and older adults during a challenging balance task where we are able to objectively corroborate changes in attentional focus; using an electroencephalography (EEG) method previously identified as an objective indicator of conscious movement control. This method assesses the neural coherence, or ‘communication’, between T3 (verbal-analytical) and Fz (motor-planning) regions of the brain. Thirty-nine young and 40 older adults performed a challenging balance task while holding a 2-meter pole under two randomised conditions: Baseline and Internal focus of attention (directing attention internally towards movement production). Results showed that young adults demonstrated increased EEG T3-Fz coherence in conjunction with increased sway path during the Internal focus condition. However, no significant differences were observed in older adults between conditions for any measure. The current study provides supporting evidence for the detrimental effect that adopting an Internal focus can have on postural control—especially in populations able govern these processes in a relatively ‘automatic’ manner (e.g., young adults). However, this work illustrates that such observations may not readily translate between populations and are not robust to age-related changes. Further work is necessary to examine mechanisms underlying this clear translational issue.